Принцип золотого сечения в контексте количественного оценивания здоровья. Нормо-индекс - Белов, В.М.; Котова, А.Б.; Кифоренко, С.И. (Управляющие системы и машины, 2016)
Решена проблема повышения разрешающей способности диагностической шкалы индексирования состояния здоровья человека путем введения дополнительного диапазона. Рассмотрен алгоритм определения границ этого диапазона. Пример подтверждает адекватность применения правила золотого сечения. Вирішено проблему підвищення роздільної здатності діагностичної шкали індексування стану здоров’я людини шляхом введення додаткового діапазону. Розглянуто алгоритм визначення границь цього діапазону. Приклад є підтвердженням адекватності застосування правила золотого перетину. Introduction. This article is aimed at developing a methodology multi-purpose information technology assessment of personal health maintenance and management of practically healthy person to form the theoretical basis of the fundamental importance of this issue. Purpose. Within the information technology diagnostics and quantitative evaluation of the provision of health information needed to develop an algorithm for estimating the state of health of the person, that would increase the accuracy of diagnosis of the index of human health. To solve the problem of increasing the resolution of the diagnostic scale index of human health through the introduction of additional normal range index. Norma index – a full-scale quantitative measure of the state of human health and the systems at various levels of the hierarchy of its components, which indicates the allowable reserve capacity of the organism as a whole, which still allow you to enter the state of human health in the border received the physiological norm. Some authors (I.V.Muravov, V.P.Petlenko etc.) considered index as a measure of the rate of life of the organism to specific environmental conditions, the range within which the quantitative changes in the oscillation of physiological processes do not lead to a new quality – the pathological process. This extended interpretation of the norms implicitly involves us and introduced a range of changes in the rate index. The concept of standard-index - is, in fact, the extra range, which allows to increase the resolution of the diagnostic scale indexing health. Methods. Algorithm for calculating the norm – the index is based on the rule of the golden section. The article gives the examples of calculation boundaries normal range – an index to the heart rate and blood sugar levels. Calculations have shown that on the scales of the maximum and minimum changes in heart rate, there are some so-called reference points – four known reference points (minimum and maximum heart rate, minimum and maximum heart rate the physiological norm). They added, obtained by calculation according to the rule of the golden section, two previously unknown, the values of the boundaries of the normal range – the index: the right of the maximum heart rate and physiological norm on the left of the minimum physiological limits of heart rate. Results. Thus, the scale of change in heart rate gained another two reference points – quantitative values boundaries normal range index, characterizing the state of health of the person, which indicates the permissible reserve-adaptive capabilities of the organism as a whole. Calculates the interest rate index of blood sugar confirmed the adequacy of the rules of the golden ratio, as calculated data coincide with the data obtained on a large array of empirical early diagnosis of diabetes. Conclusions. It was proved that the range of physiological norm and pathology is the range when the figure has already gone beyond the physiological norms, but still retains the ability to connect due to adaptation and reserve capacity of the body to enter a state of human health in the border accepted norm. The introduction of the norm-index concept as a full-scale quantitative indicator, has increased the resolution of the diagnostic scale index of human health and the systems at various levels of the hierarchy of its components, the upper limit which shows allowable reserve capacity of the body and the whole person.